Measurement of particle size using electrostatic sensors - Fahisal, Abdullah; Mohd Fua’ad, Haji Rahmat (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/